Exposure to nanoparticles of magnetite Fe3O4 in three different doses and their influence on selected respiratory parameters of bronchoalveolar lavage after intravenous instillation - Hurbánková, Marta; Volkovová, Katarína; Černá, Silvia; Wimmerová, Soňa; Moricová, Štefánia (Central European journal of public health, 2023)
OBJECTIVES: Due to nano-dimensions (less than 100 nm), can nanoparticles probably penetrate through various membranes and travel from the bloodstream to other organs in the body. The aim of our study was to find out whether NPs Fe3O4 (coated with sodium oleate) injected into the tail vein of laboratory Wistar rats pass through the bloodstream to the respiratory tract (in comparison with a control group); and if so whether increasing doses of NPs Fe3O4 have an escalating harmful effect on selected bronchoalveolar lavage (BAL) parameters. METHODS: Wistar rats were intravenously given 3 doses of the suspension of NPs Fe3O4 (0.1% LD50 = 0.0364, 1.0% = 0.364 and 10.0% = 3.64 mg/kg animal body weight). Seven days later, we sacrificed the animals under anaesthesia, performed bronchoalveolar lavage (BAL), and isolated the collected cells. Many inflammatory and cytotoxic BAL parameters were examined. RESULTS: Both inflammatory and cytotoxic BAL parameters affected by Fe3O4 suspension were changed compared to control results, but not all were statistically significant. Thus, the NPs Fe3O4 passed through the bloodstream to the respiratory tract and affected it. The highest concentration of NPs Fe3O4 (10%) had the most influence on BAL parameters (7 of 12 parameters). Only 3 parameters showed a pure dose dependence. CONCLUSION: We assume that the adverse effect of Fe3O4 NPs in our study is probably not correlated with the dose, but rather with the size of the particles or with their surface area.
Keywords: inflammatory and cytotoxic parameters; bronchoalveolární lavážní tekutina; nanočástice; Rats; oxid železnato-železitý; Administration, Intravenous; potkani Wistar; Animals; dose dependence; intravenózní podání; bronchoalveolar lavage; zvířata; Nanoparticles; krysa rodu Rattus; Rats, Wistar; Bronchoalveolar Lavage Fluid; bronchoalveolární laváž; nanoparticles; Bronchoalveolar Lavage; Ferrosoferric Oxide